Preparation of high-flowability ultra-early-strength grouting material and investigation of its mechanical properties in reinforcing fractured sandstone - Yijiang Zong; Dong Zhu; Liang Yue; Xiangling Tao; Min Chen (PLoS ONE, 2025)
This study systematically investigated the effects of modified ultrafine fly ash, ultrafine silica fume, nano-SiO2, and polycarboxylate superplasticizer on the performance of cement-based grouting materials. Using a five-level orthogonal experimental, the optimal mix ratio was determined: 5.00 wt.% modified ultrafine fly ash, 10.00 wt.% ultrafine silica fume, 9.00 wt.% nano-SiO2, and 0.05 wt.% polycarboxylate superplasticizer. This formulation enabled the preparation of a cement-based grouting material with high-flowability and ultra-early-strength (HFUES) characteristics. Experimental results demonstrated that, compared to ordinary silicate grouting materials, the HFUES grouting material significantly enhanced the reinforcement of fractured sandstone. The reinforced specimens exhibited an average 67.42% increment in tensile strength, 123.17% increment in the uniaxial compressive strength, and 94.00% increment in elastic modulus compared to intact specimens. Microstructural analysis revealed that the grouting material was uniformly distributed within the sandstone matrix, forming a dense interfacial bond and generating a substantial amount of fibrous network-like hydration products. The volume fraction of the consolidated matrix was 1.33–1.47 times that of ordinary silicate grouting materials, while the fracture volume fraction was only 0.36–0.73 times. The study demonstrates that the HFUES grouting material exhibits excellent mechanical properties and interfacial bonding characteristics, significantly improving the reinforcement effectiveness of fractured sandstone.